Fraud diamond analysis in detecting financial statement fraud - Muara Rizqulloh Noble (STIE Perbanas Surabaya, 2019)
This study aimed to analyze the factors used to detect financial statement fraud from a fraud diamond perspective. It tried to find out the effect of pressure proxied by financial targets, opportunity proxied by ineffective monitoring, rationalization proxied by change in auditors, and capability proxied by director change on financial statement fraud. It used 36 mining companies listed on the Indonesia Stock Exchange (IDX) period 2014-2016 as the sample. This sample was taken using a purposive sampling technique and data analysis were analyzed using multiple linear regression. The results indicate that pressure proxied by financial targets and rationalization proxied by change in auditors have an effect on financial statement fraud, whereas opportunity proxied by ineffective monitoring and capability proxied by replacement of directors have no effect on financial statement fraud.